2002
DOI: 10.1161/01.str.0000033130.82164.24
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tibolone and Conjugated Equine Estrogens Effects on Carotid Artery Atherosclerosis of Postmenopausal Monkeys

Abstract: Background and Purpose-Tibolone is a tissue-specific compound that has favorable effects on bone and menopausal symptoms without stimulating endometrium or breast, but lowers concentrations of plasma high-density lipoprotein (HDL) cholesterol (HDLC). This study was designed to determine whether the HDL lowering with tibolone exacerbated common or internal carotid artery atherosclerosis and to evaluate tibolone treatment relative to conjugated equine estrogens (CEE) alone or in combination with medroxyprogester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
12
1
2
Order By: Relevance
“…39 Images of stained sections were captured using a Hammamatsu NanoZoomer digital slide scanner. Intimal area (IA; mm 2 ) and maximum medial thickness (MXMT; mm) were measured as described previously 44 using Image-Pro Plus version 9.1 imaging software (Media Cybernetics Inc, Bethesda, MD). For consistency one investigator (MGSM) measured all arteries, blinded to treatment.…”
Section: Methodsmentioning
confidence: 99%
“…39 Images of stained sections were captured using a Hammamatsu NanoZoomer digital slide scanner. Intimal area (IA; mm 2 ) and maximum medial thickness (MXMT; mm) were measured as described previously 44 using Image-Pro Plus version 9.1 imaging software (Media Cybernetics Inc, Bethesda, MD). For consistency one investigator (MGSM) measured all arteries, blinded to treatment.…”
Section: Methodsmentioning
confidence: 99%
“…4). Comparable plasma levels of the unconjugated tibolone metabolites have previously been found in cynomolgus monkeys given 0.2 mg/kg/day [45][46][47][48] and in postmenopausal women [29][30][31][32][33] treated with 2.5 mg/day. From the individual concentration-time curves, the area under the curve (AUC) values have been calculated and the AUCs of metabolites with similar endocrine effects have been combined: tibolone and 4 -tib (both having androgenic and progestagenic activities); 3␣OH-tib and 3␤OH-tib (both oestrogenic), 3␣ and 3␤ mono-S tib (both inactive, but may be reversed to the corresponding active hydroxy metabolites) and 3␣ and 3␤ diS (both inactive).…”
Section: Observations In Plasma Heart and Livermentioning
confidence: 52%
“…The study was approved by the Institutional Animal Care and Use Committee, performed at Huntingdon Life Sciences (USA and UK) and complied with the Animal Welfare Act Regulations and Good Laboratory Practice standards. The cynomolgus monkeys have been selected in view of their marked similarity to humans as found in a previous study with monkeys fed an atherogenic diet demonstrating protection by tibolone against bone loss, without stimulation of the breast and endometrium [45][46][47][48]. After receiving tibolone (Org OD14, 0.5 mg/kg/day by nasogastric gavage) for 36 days, one monkey was euthanized and autopsied at each of the following times: 1, 1.25, 2.25, 4, 6 and 24 h after the final dose.…”
Section: Design Of the Studymentioning
confidence: 99%
“…Indeed, in a rabbit model, Zandberg et al (9) demonstrated that tibolone prevents high-cholesterol, diet-induced atherosclerosis (cholesterol accumulation in the aortic arch, fatty streak, and foam cell formation) and neointimal thickening both in the presence and absence of endothelial lesions. Similarly, Clarkson et al (25) demonstrated that decreases in HDL levels in response to tibolone did not increase coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 91%